Olfaction, valuation, and action: reorienting perception - Castro, Jason B.; Seeley, William P. (Frontiers in Psychology, 2014)
In the philosophy of perception, olfaction is the perennial problem child, presenting a range of difficulties to those seeking to define its proper referents, and its phenomenological content. Here, we argue that many of these difficulties can be resolved by recognizing the object-like representation of odors in the brain, and by postulating that the basic objects of olfaction are best defined by their biological value to the organism, rather than physico-chemical dimensions of stimuli. Building on this organism-centered account, we speculate that the phenomenological space of olfaction is organized into a number of coarse affective dimensions that apply categorically. This organization may be especially useful for coupling sensation to decision-making and instrumental action in a sensory modality where the stimulus space is especially complex and high-dimensional.